Pengambilan Keputusan Pasien untuk Rawat Inap di Rumah Sakit X Jakarta - Hafidzulla, Zul; Wekadigunawan, CSP (Journal of Hospital Management, 2021)
The low BOR of X hospitals in Jakarta reaches only 19% in 2018 (the ideal achievement of BOR hospitals in Indonesia is 60% - 85%). While the community's need for inpatient facilities is still high. Seen from the Bed Ratio in Indonesia is still quite low at 1.04 beds per 1000 population (ideal above 4/1000). This study is to assess and obtain empirical evidence of the influence of several variables on the patient's decision to do hospitalization. Will analyze the factors of health personnel attitudes, patient confidence in the quality of service, and patient subjective norms. The method used is multiple correlation models, quantitative approaches, correlational techniques, and using primary data. The time dimension is one shot study. Data collection is a survey method. The analysis tool uses multiple linear regression. The research data in the form of patient subject data that express opinions, attitudes, justifications, experiences, or characteristics of the subject in the decision to be hospitalized in hospital X Jakarta. Respondents are inpatients at X Jakarta hospital. Unit of analysis is individual. The results showed that the attitude of health workers, and subjective norm of patients affect the patient's decision to be hospitalized; patient beliefs on the service quality does not affect the patient's decision to be hospitalized; and all variables simultaneously affect the patient's decision to be hospitalized. The attitude of health workers is most influential on the patient's decision to be hospitalized. Intrinsic factors also have a dominant influence. In the research findings, it was found that patients believed more information about this hospital that was obtained from patient friends, and patients were influenced by religious factors in deciding to use inpatient facilities at this hospital. Patients' lowest confidence in information is given by families about the hospital, and patients are not influenced by their social status in deciding to be hospitalized.Keywords: health workers attitude, patient beliefs on service quality, patient subjective norm, patient decesions to be hospitalized